As estratégias de um milhão - Roque, Aguiobey de Souza (2020)
This work presents the content of financial mathematics, which is presented in high school in a superficial way, where its examples are neither practical nor real, which hinders interest and learning. We managed to observe many financial decisions all wrongly, so in this work we report situations in which we can use financial mathematics to make better decisions in life. We show some savings (basic concepts), financing, financing systems, investments and strategies for the accumulation of equity. The work aims to show a comparison between three strategies for the accumulation of equity that have the same financial effort in their realization. At the end of each strategy, the accumulated equity includes a property and a sum of money, the difference of which reaches up to 32.5 % in favor of the winning strategy.